2020
DOI: 10.3390/ijerph17103390
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Evaluation through Infrared Thermography: Development and Proposal of a Rapid Screening Tool for Risk Assessment Arising from Repetitive Actions of the Upper Limbs

Abstract: Risk analysis is one of the main tools for preventing the occurrence of Work-Related Musculoskeletal Disorders. New methods of risk analysis should seek to be more agile and simplified, encouraging them to be widely applied in work environments. This paper aimed to develop a rapid tool for assessing the risk of developing Work-Related Musculoskeletal Disorders (WMSDs) arising from repetitive actions of the upper limbs, while using a thermographic camera to measure skin temperature variation. A workstation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…One of the findings of this research shows that both techniques are useful for assessing skin temperature and identifying rapid changes in skin temperature, because they can predict the presence of musculoskeletal disorders [ 11 , 51 ]. Previous studies have shown that acute injury causes an increase in permanent blood flow, which implies increased metabolic activity, as demonstrated in this study [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the findings of this research shows that both techniques are useful for assessing skin temperature and identifying rapid changes in skin temperature, because they can predict the presence of musculoskeletal disorders [ 11 , 51 ]. Previous studies have shown that acute injury causes an increase in permanent blood flow, which implies increased metabolic activity, as demonstrated in this study [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Para la evaluación de los impactos de las tareas repetitivas en los trabajadores se han desarrollado y aplicado técnicas y metodologías generales que incluyen factores ergonómicos para disminuir la probabilidad de las lesiones. Estas técnicas actúan de manera preventiva en las estaciones de trabajo, lo que mejora el desempeño de los trabajadores y la funcionalidad sus estaciones de trabajo (Ring & Ammer, 2012;Soares et al, 2020). Por otro lado, existe un conjunto de métodos comunes que evalúan la carga muscoesquelética y los riesgos de desarrollar lesiones muscoesqueléticas, los cuales determinan valores de entrada de la carga externa e interna en las distintas partes del cuerpo (Sousa et al, 2017).…”
Section: Introductionunclassified
“…When MSDs are caused by work-related issues, they are called work-related musculoskeletal disorders (WMSDs) [ 4 ]. For years, studies have focused on ways to reduce WMSDs.…”
Section: Introductionmentioning
confidence: 99%